The Effects of Nicotine on PGI2 Production by Rat Aortic Endothelium - Bull, H A; Pittilo, R M; Blow, D J; Blow, C M; Rowles, P M; Woolf, N; Machin, S J (Thrombosis and Haemostasis, 1985)
The production of prostacyclin by rat aortic rings was measured following administration of nicotine by a single subcutaneous injection and after continuous subcutaneous infusion over 7 days. Single subcutaneous injections of nicotine at 1, 5, 10 or 20 mg/kg had no effect on prostacyclin production by rat aortic rings in comparison with controls. However, aortic rings obtained after 7 days continuous subcutaneous infusion of 0.54 g/ml of nicotine at the rate of 1 μl per hour produced significantly less prostacyclin than control animals.
Keywords: Nicotine; Prostacyclin; Endothelium